Development, Validation and Comparison of Artificial Neural Network Models and Logistic Regression Models Predicting Survival of Unresectable Pancreatic Cancer - Tong, Zhou; Liu, Yu; Ma, Hongtao; Zhang, Jindi; Lin, Bo; Bao, Xuanwen; Xu, Xiaoting; Gu, Changhao; Zheng, Yi; Liu, Lulu; Fang, Weijia; Deng, Shuiguang; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Prediction models for the overall survival of pancreatic cancer remain unsatisfactory. We aimed to explore artificial neural networks (ANNs) modelling to predict the survival of unresectable pancreatic cancer patients. Methods: Thirty-two clinical parameters were collected from 221 unresectable pancreatic cancer patients, and their prognostic ability was evaluated using univariate and multivariate logistic regression. ANN and logistic regression (LR) models were developed on a training group (168 patients), and the area under the ROC curve (AUC) was used for comparison of the ANN and LR models. The models were further tested on the testing group (53 patients), and k-statistics were used for accuracy comparison. Results: We built three ANN models, based on 3, 7 and 32 basic features, to predict 8-month survival. All 3 ANN models showed better performance, with AUCs significantly higher than those from the respective LR models (0.811 vs. 0.680, 0.844 vs. 0.722, 0.921 vs. 0.849, all p<0.05). The ability of the ANN models to discriminate 8-month survival with higher accuracy than the respective LR models was further confirmed in 53 consecutive patients. Conclusion: We developed ANN models predicting the 8-month survival of unresectable pancreatic cancer patients. These models may help to optimize personalized patient management.